Management of native and exotic plant species with edible fruits in a rural community in a protected area of NW Patagonia - Chamorro, Melina F.; Ladio, Ana H. (Ethnobiology and Conservation, 2021)
Management practices are very sensitive to socio-environmental change and the influence of market society. This case study was carried out in the Cuyín Manzano rural community, situated in a protected area within the North Patagonian UNESCO biosphere reserve. We investigate the differential practices applied by the community with regard to management of native and introduced species with edible fruits using semi-structured and free interviews in 11 homes (80%). A Participatory Rural Appraisal (PRA) was also performed to validate the field results. The data was analyzed quali-quantitatively, in the latter case with Generalized Linear Models. A total richness of 27 species was found, of which 11 were native and 17 introduced. Native plants were mainly managed by gathering and tolerance, while exotic species were not only harvested, but also protected, sown and transplanted, and plants inherited from forebears were cared for. Management intensity varied according to origin, being greater for the introduced species. In addition, the species of greater cultural importance were also those which experienced a higher number of management practices, with possible processes of incipient domestication being particularly notable for two native plants. Exotic plants have a higher probability of being managed, and with greater intensity, than native ones, even though the latter have had a much longer history of use. Our results show patterns of diversification of edible fruit species through different management practices. For inhabitants, these practices represent significant situations of contact with nature, which enable traditions based on local knowledge to be maintained.